Efficacy of Antitranspirant on the Relative Water Content and Vegetative Growth of Tomato - Das, T.K.; Mohanty, C.R. (Journal of Soil and Water Conservation, 2022)
An experiment was carried out at the Horticultural Research Station of Orissa University of Agriculture and Technology, Bhubaneswar on the effect of the antitranspirant (Phenyl Mercuric Acetate - PMA) on the vegetative growth and relative water content of tomato. It was observed that the relative water content of the tomato leaves increased significantly with the varying concentrations of PMA. Spraying of PMA at the rate of 10-4 M at 30 DAT + 60 DAT produced the highest R. IV C (i.e. S5C2 produced 89.838). PMA sprayed tomato plants produced excellent vegetative growth. PMA at the rate of I 0-4M at 30 DAT + 60 DAT produced the maximum plant height of 53.12 cm. maximum number of branches per plant i.e., 10.47 and MaX1-11111171 number of leaves per plant i.e., 73.62.